EuReCa ONE—27 Nations, ONE Europe, ONE Registry: A prospective one month analysis of out-of-hospital cardiac arrest outcomes in 27 countries in Europe. (August 2016) - Gräsner, Jan-Thorsten; Lefering, Rolf; Koster, Rudolph W.; Masterson, Siobhán; Böttiger, Bernd W.; Herlitz, Johan; Wnent, Jan; Tjelmeland, Ingvild B.M.; Ortiz, Fernando Rosell; Maurer, Holger; Baubin, Michael; Mols, Pierre; et al.
Abstract: Introduction: The aim of the EuReCa ONE study was to determine the incidence, process, and outcome for out of hospital cardiac arrest (OHCA) throughout Europe. Methods: This was an international, prospective, multi-centre one-month study. Patients who suffered an OHCA during October 2014 who were attended and/or treated by an Emergency Medical Service (EMS) were eligible for inclusion in the study. Data were extracted from national, regional or local registries. Results: Data on 10, 682 confirmed OHCAs from 248 regions in 27 countries, covering an estimated population of 174 million. In 7146 (66%) cases, CPR was started by a bystander or by the EMS. The incidence of CPR attempts ranged from 19.0 to 104.0 per 100, 000 population per year. 1735 had ROSC on arrival at hospital (25.2%), Overall, 662/6414 (10.3%) in all cases with CPR attempted survived for at least 30 days or to hospital discharge. Conclusion: The results of EuReCa ONE highlight that OHCA is still a major public health problem accounting for a substantial number of deaths in Europe. EuReCa ONE very clearly demonstrates marked differences in the processes for data collection and reported outcomes following OHCA all over Europe. Using these data and analyses, different countries, regions, systems, and concepts can benchmark themselves and may learn from each other to further improve survival following one of our major health care events.